Exploring Strategies to Support Adolescent Mental Health after Parental Divorce: A Scoping Review - Edna Rich; Letitia Butler-Kruger; Nicolette Roman (Youth, 2023)
The recent acceleration in divorce rates and diversification of nuclear families has resulted in an increase in single-parent households. Divorce is one of the most adverse events in a child’s life. Various literature highlights the detrimental effects of parental divorce on children and adolescents, but few studies have emphasized possible support strategies or interventions available to assist in the mental health of adolescents after divorce. The objective of this study was to gain an overview of the strategies and interventions available to adolescents exposed to parental divorce. The current study employed a scoping review method to evaluate the coverage of literature on strategies available to support adolescent mental health after parental divorce. The following databases were searched: Academic Search Premier, Africa-Wide Information, African Journal Online, CINAHL, and JSTOR. A total of eight studies were included in this review. The results show that most mental health interventions target the known mediator of risk, such as parenting problems or family conflict. Although the parents, caregivers, or teachers of these adolescents reported improvement after the intervention, the adolescents reported no effect.